2009
DOI: 10.1093/carcin/bgp068
|View full text |Cite
|
Sign up to set email alerts
|

Time-point and dosage of gene inactivation determine the tumor spectrum in conditional Ptch knockouts

Abstract: Mutations in Patched (PTCH) have been associated with tumors characteristic both for children [medulloblastoma (MB) and rhabdomyosarcoma (RMS)] and for elderly [basal cell carcinoma (BCC)]. The determinants of the variability in tumor onset and histology are unknown. We investigated the effects of the time-point and dosage of Ptch inactivation on tumor spectrum using conditional Ptch-knockout mice. Ptch heterozygosity induced prenatally resulted in the formation of RMS, which was accompanied by the silencing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(85 citation statements)
references
References 35 publications
1
81
0
1
Order By: Relevance
“…Unexpectedly, we found that only a minority of ERMS originated from committed muscle cells, which express the myogenic factor Myf5, suggesting that uncommitted precursor cells represent the main source of ERMS. Previous studies from our laboratory revealed that postnatal monoallelic inactivation of Ptch does not suffice to initiate ERMS (Zibat et al, 2009) indicating that cell populations that arise postnatally, such as side population cells, circulating myeloid cells or mesenchymal stem cells of the bone marrow, and satellite cells of the adult skeletal muscle do not contribute significantly to ERMS. Satellite cells have also been excluded by another study in which Cre/Lox inactivation of Ptch using a Pax7-Cre knock-in did not cause ERMS (Taniguchi et al, 2009).…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Unexpectedly, we found that only a minority of ERMS originated from committed muscle cells, which express the myogenic factor Myf5, suggesting that uncommitted precursor cells represent the main source of ERMS. Previous studies from our laboratory revealed that postnatal monoallelic inactivation of Ptch does not suffice to initiate ERMS (Zibat et al, 2009) indicating that cell populations that arise postnatally, such as side population cells, circulating myeloid cells or mesenchymal stem cells of the bone marrow, and satellite cells of the adult skeletal muscle do not contribute significantly to ERMS. Satellite cells have also been excluded by another study in which Cre/Lox inactivation of Ptch using a Pax7-Cre knock-in did not cause ERMS (Taniguchi et al, 2009).…”
Section: Discussionmentioning
confidence: 85%
“…Injection of tamoxifen at any embryonal stage resulted in expression of Ptch del transcripts in all examined organs in the adult (Figure 1d). Expression intensity of mutant Ptch del transcripts in these organs was indistinguishable from Ptch del/ þ mice, in which exons 8 and 9 of Ptch had been deleted in the germline (data for Ptch del/ þ mice have been published before (Zibat et al, 2009)). …”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations